The relation between economic and non-economic incentives to work and employment chances among the unemployed - Madelene Nordlund; Mattias Strandh (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
In this study we address the relationship of self-reported reservation wages (RW) (the lowest offered income at which an unemployed persona will accept a job offer), the income replacement rate of unemployment benefit (IRUB) and psychosocial need for employment with job search intensity and reemployment probabilities among unemployed in Sweden in 1996-1997. The results indicate that the RWs reported by the group that we observe over time were relatively stable, but strongly related to IRUB and both the gender and age of the unemployed individuals. Interestingly, IRUB was related to search intensity, but not reemployment probabilities, while the RW was related to reemployment probabilities but not search intensity. These findings suggest that IRUB might be a poor proxy for RWs, in some situations at least. In sharp contrast, psychosocial incentives appeared to be related to both search intensity and reemployment probabilities, indicating a need for a richer understanding of search behaviour and unemployment durations. The data also indicate that the roles of search behaviour and incentives for reemployment probabilities may be exaggerated which, at least under the relatively depressed labour market conditions our data represented, appeared to be much more strongly related to human capital and demand for labour for our study population.
Keywords: J2; J3; J64; 330; reservation wage; income replacement rate; psychosocial need of work; job search intensity; human capital; job-chances